Pathogenic Neisseria hitchhike on the uropod of human neutrophils. - Niklas Söderholm (Public Library of Science (PLoS), 2011)
Polymorphonuclear neutrophils (PMNs) are important components of the human innate immune system and are rapidly recruited at the site of bacterial infection. Despite the effective phagocytic activity of PMNs, Neisseria gonorrhoeae infections are characterized by high survival within PMNs. We reveal a novel type IV pilus-mediated adherence of pathogenic Neisseria to the uropod (the rear) of polarized PMNs. The direct pilus-uropod interaction was visualized by scanning electron microscopy and total internal reflection fluorescence (TIRF) microscopy. We showed that N. meningitidis adhesion to the PMN uropod depended on both pilus-associated proteins PilC1 and PilC2, while N. gonorrhoeae adhesion did not. Bacterial adhesion elicited accumulation of the complement regulator CD46, but not I-domain-containing integrins, beneath the adherent bacterial microcolony. Electrographs and live-cell imaging of PMNs suggested that bacterial adherence to the uropod is followed by internalization into PMNs via the uropod. We also present data showing that pathogenic Neisseria can hitchhike on PMNs to hide from their phagocytic activity as well as to facilitate the spread of the pathogen through the epithelial cell layer.